Zika Virus Promotes Neuronal Cell Death in a Non-Cell Autonomous Manner by Triggering the Release of Neurotoxic Factors - Olmo, Isabella G.; Carvalho, Toniana G.; Costa, Vivian V.; Alves-Silva, Juliana; Ferrari, Carolina Z.; Izidoro-Toledo, Tatiane C.; da Silva, Juliana F.; Teixeira, Antonio L.; Souza, Danielle G.; Marques, Joao T.; Teixeira, Mauro M.; Vieira, Luciene B.; et al. (Frontiers in Immunology, 2017)
Zika virus (ZIKV) has recently caused a worldwide outbreak of infections associated with severe neurological complications, including microcephaly in infants born from infected mothers. ZIKV exhibits high neurotropism and promotes neuroinflammation and neuronal cell death. We have recently demonstrated that N-methyl-d-aspartate receptor (NMDAR) blockade by memantine prevents ZIKV-induced neuronal cell death. Here, we show that ZIKV induces apoptosis in a non-cell autonomous manner, triggering cell death of uninfected neurons by releasing cytotoxic factors. Neuronal cultures infected with ZIKV exhibit increased levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and glutamate. Moreover, infected neurons exhibit increased expression of GluN2B and augmented intracellular Ca2+ concentration. Blockade of GluN2B-containing NMDAR by ifenprodil normalizes Ca2+ levels and rescues neuronal cell death. Notably, TNF-α and IL-1β blockade decreases ZIKV-induced Ca2+ flux through GluN2B-containing NMDARs and reduces neuronal cell death, indicating that these cytokines might contribute to NMDAR sensitization and neurotoxicity. In addition, ZIKV-infected cultures treated with ifenprodil exhibits increased activation of the neuroprotective pathway including extracellular signal-regulated kinase and cAMP response element-binding protein, which may underlie ifenprodil-mediated neuroprotection. Together, our data shed some light on the neurotoxic mechanisms triggered by ZIKV and begin to elucidate how GluN2B-containing NMDAR blockade can prevent neurotoxicity.